(untitled) (MAUSAM, 2007)
ABSTRACT. The trials of district level forecasts yielded encouraging results during 2005 monsoon. The purpose of this paper is to document the methodology followed in the value addition during the periods of monsoon depressions and storms. The focus is on the use of Mean Sea Level (MSL) positions and the 850 hPa circulation features predicted by different model centres, especially the European Centre for Medium-Range Weather Forecasts (ECMWF). The ECMWF-predicted 72 hr MSL position of the monsoon depression centre was found to be significantly correlated to the actual position of the system and the central location of the realized rainfall zone associated with the system. Even the predicted location of the system at 850 hPa by the ECMWF has been found useful in identifying the districts that received heaviest rainfall associated with the monsoon systems. MM5 and T-80 – predicted locations of the system at 850 hPa yielded lower correlations with the location of the actual rainfall zone associated with the system. As ECMWF – predicted rainfall was not available the rainfall predicted by MM5 and T-80 were used in the computations of the correlations with actual rainfall amounts associated with monsoon depressions and storms. The correlations between MM5 and T-80 – predicted average and maximum rainfall associated with systems and corresponding actual were poor. Though it is not difficult to identify the districts that are likely to be affected by the heavy rainfall associated with monsoon depressions/storms, the prediction of exact rainfall amount for each district (beyond heavy, very heavy or exceptionally heavy categories) is difficult from the model outputs which makes such forecasts a very challenging task. Therefore, the value addition using other inputs such as satellite information, synoptic charts, climatology etc. are very useful in the prediction of rainfall amounts associated with monsoon systems.